Accelerate thermal modernization of buildings with minimum standards for buildings and binding retrofitting targets - Sophie M. Behr; Merve Kucuk; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
The energy and climate crisis enhance the need for energy savings. In the building sector, these savings can be achieved primarily through thermal retrofitting. So far, progress in this area has been slow. To date, less than one percent of the residential building stock in Germany is retrofitted each year. The existing support programs alone offer too little reliability for the necessary investments in additional production capacities for building materials and in the construction sector to take place. In order to accelerate the energetic modernization of buildings, minimum energy performance standards (MEPS) for buildings and binding target for the annual rate of thermal building retrofitting is necessary. Low-income households in particular could be sustainably protected from future energy cost shocks and gas savings of up to 14 percent could be achieved by end of 2025.
Keywords: 330; Climate policy; Real estate and housing; Energy economics